Social Sustainability of High-Rise Buildings - Mahdavinejad, Mohammad Javad; Sadraie, Ali; Sadraie, Golrokh (Journal of Social Economics Research, 2014)
Nowadays, High-rise building is proposed as a dominant form in world’s Major cities which its rapid growth has caused social and cultural concerns of the residents of these buildings. Social capital is remembered as a basis for economic development of any society. Its importance can be seen in the economic development of developing countries. Social capital is the invisible wealth of a country that encompasses institutions, relationships and norms that shape social interactions. In this paper, we try to achieve points in the social issues of these buildings with architectural principles and standards. For this purpose, we has been examined the relationship between the three elements of social capital, networks, confidence, partnership and architectural elements such as natural light, security, natural ventilation, visibility, space variability, physical identity, exterior solemnity, quality of entrance and lobby, quantity and quality of roadway and pedestrian access, beautiful landscaping and transfer of the annoying sounds in a number of samples. In this study we have chosen 9 high-rise building in Shiraz (one of the major cities of Iran) and to evaluate them in terms of social capital and architecture in two ways of Observation and navigation (questioning residents by Questionnaire and sampling) which Finally substantially points were achieved in the design of high-rise buildings.